Operational Standards for Water Quality Management and Vannamei Shrimp Hatchery Process at PT. Esaputlii Main Initiative of Barru Regency - Muhammad Bibin; Ferdi Anggara; Futri Syahrir; Nur Zafitri; Sukmawati Sukmawati (Jurnal Media Akuakultur Indonesia, 2025)
Vannamei shrimp or Litopanaeus vannamei is a species of shrimp native to the waters of central and south America, such as Ecuador, Vanezuela, Panama, and Brazil. It was cultivated in Indonesia in 2001 to replace the species Litopanaeus monodon, which experienced decline and production failures due to poor water quality and disease risk. The purpose of this study is to find the water quality management method used to produce vannamei shrimp larvae (Litopenaeus vannamei) in PT. Esaputlii Prakarsa Utama, Barru Regency. The activity was carried out through a participatory approach and direct observation for 4 months (February to May 2025). The results of the study revealed that (1) Strict sanitation of production containers (brood rearing tanks, egg hatching, larvae, and feed cultures) with 100 ppm of chlorine was used; (2) Integrated seawater and freshwater resource management (salinity 30–33 ppt, pH 7–8.3); (3) Routine monitoring of water quality parameters (temperature: 31–34 °C, salinity: 30–32 g/L, pH: 8.1–8.5, alkalinity: 128–152 mg/L); and (4) Operational techniques such as flowthrough in the mother tank and gradual water replacement (10–30%) in the larval tank. If this can be applied to small-scale vannamei shrimp farmers in Barru Regency, it can certainly improve the quality of fry production.